Exploring Female Pre-Service EFL Teacher’s Experiences with Content-Based Instruction: A Narrative Inquiry - Dwi Safitri Mariesta Isnaini; Sayyidatul Fadlilah; Ikhrom Ikhrom (At-Taqaddum, 2022)
The common problem of primary teachers in class situation is to create an effective learning environment by involving their competence to connect rational understanding, conceptual approaches, and adaptive considerations in delivering content material. In addition, the implementation of CBI in the context of teaching foreign languages requires teachers to have the ability to design content-based lesson planning and emphasize language skills. The study involved narrative research to explore the pre-working EFL female teacher experience with content-based instruction during the teacher preparation program. The study is based on theoretical concepts related to the professional knowledge of teachers about EFL and PCK (Pedagogical Content Knowledge) as the way EFL teachers describe their pedagogical knowledge. Data is obtained from various sources like: interviews, post-observation, learning diary, autobiography, and personal accounts. The data is then analyzed to generate evidence of how the participant actively applies CBI in teaching practice placement, how he creates class situation, and his aspirations about the future career of CBI. Three experience teachers of foreign language students with content-based instruction: exploring the identity/innovation interface” claim that the PCK enables students-teachers to implement CBI successfully.